NATURE OF HOME-GROWN TERRORISM THREAT IN GHANA - Zulkarnain, Mohammed (UI Scholars Hub, 2020)
The present state of security in the West African sub-region raises important issues of the nature of home-grown terrorism (HGT) threats in Ghana. Most studies of home-grown terrorism have focused mainly on the psychological implications of terrorist acts. This paper examines the complexities of the Ghanaian state securities perceive the nature of the threat of home-grown terrorism in the country. Data was collected from representatives of the state security agencies using semi-structured in-depth interviews. Findings indicate that the threat nature of home-grown terrorism in Ghana varies but the most significant is the threat from the recruitment of Ghanaian Muslims by the so-called Islamic State in Iraq and Syria (ISIS). The finding helps to gain a better understanding of the difficulty of living under constant home-grown terrorism threats. It also provides an understanding of how citizens cope with and adjust to such threats.